Faktor-Faktor yang Mempengaruhi Keberlanjutan Ruang Terbuka Hijau di DKI Jakarta - Suryani Purnomo; Pudji Muljono; Djoko Susanto; Sri Harijati (Jurnal Penyuluhan, 2021)
The quantity and quality of green open space (RTH) in big cities in Indonesia has decreased and resulted in environmental damage. The existence of green space is very much needed by the people of DKI Jakarta. However, the availability has not met the standards set by law, it is suspected that the capacity of RTH managers and the role of stakeholders in encouraging land use for RTH sustainability is not maximized. This study aims to analyze the level of sustainability of RTH and analyze the factors that influence the sustainability of RTH in DKI Jakarta. The research method uses quantitative data with survey methods and questionnaires as a data collection tool. The number of samples taken as many as 340 people for sub-districts and villages was selected by purposive sampling with the consideration that there are green alley activities for the sustainability of RTH. Data were collected from December 2019 to February 2020. The data were analyzed descriptively using SPSS 24 and inferential PLS 3. The results showed that the level of sustainability of RTH in DKI Jakarta was in the low category on economic, ecological, socio-cultural aspects and very low category for aesthetics. Stakeholder support has a positive and real impact on the sustainability of RTH which is reflected by the role of the government, community, media and extension workers. Manager capacity also has a positive and significant impact on the sustainability of RTH which is reflected by technical, managerial and social capacities.